Kalihioxepanes A—G: Seven Kalihinene Diterpenoids from Marine Sponge Acanthella cavernosa Collected off the South China Sea. Issue 15 (30th May 2022) - Wang, Zhe; Han, Xiao; Liu, Guoping; Zhang, Di; Hou, Huiyue; Xiao, Li; de Voogd, Nicole J.; Tang, Xuli; Li, Pinglin; Li, Guoqiang
Comprehensive Summary: Seven new kalihinene diterpenoids, kalihioxepanes A—G (1—7) bearing a rare oxepane ring, were isolated from sponge Acanthella cavernosa collected from the South China Sea. The structures and absolute configurations were elucidated by comprehensive spectroscopic analysis, single crystal X‐ray diffraction, and quantum chemical calculation methods. Kalihioxepane A (1) displayed strong cytotoxicity against H69 and K562 tumor cells, while kalihioxepane B (2) showed moderate cytotoxicity against K562 cells. Abstract : Seven new kalihinene diterpenoids, kalihioxepanes A—G (1—7) bearing a rare oxepane ring, were isolated from sponge Acanthella cavernosa collected from the South China Sea. The structures and absolute configurations were elucidated by comprehensive spectroscopic analysis, single crystal X‐ray diffraction, and quantum chemical calculation methods. Kalihioxepane A (1) displayed strong cytotoxicity against H69 and K562 tumor cells, while kalihioxepane B (2) showed moderate cytotoxicity against K562 cells.